BVP for Hadamard Sequential Fractional Hybrid Differential Inclusions. (24th February 2022) - Li, Ning; Gu, Haibo; Chen, Yiru
Abstract : The study is concerned with the Hadamard sequential fractional hybrid differential inclusions with two-point hybrid integral boundary conditions. With the help of the Dhage fixed-point theorem for the product of two operators and the Covitz-Nadler fixed-point theorem in the case of fractional inclusions, we obtain the existence results of solutions for Hadamard sequential fractional hybrid differential inclusions. Finally, two examples are presented to illustrate the main results.